Evolution of a Shallow Water Wave‐Dominated Shipwreck Site: Fougueux (1805), Gulf of Cadiz. Issue 6 (17th June 2016) - Fernández‐Montblanc, T.; Quinn, R.; Izquierdo, A.; Bethencourt, M.
Abstract : The evolution of the shallow water wave‐dominated Fougueux wreck site in the Gulf of Cadiz was investigated through repeat bathymetric surveys, wave‐ and current‐velocity field measurements, and numerical modeling. This multidisciplinary approach was used to understand the relationships between scouring, morphodynamic change, and hydrodynamic forcing. Field experiments and numerical models indicate that wave processes dominate site evolution. Numerical model outputs indicate current velocity, bed shear stress, orbital velocity, and specially wave fraction breaking (with an increase of 45% and 135% for weak and significant storm conditions, respectively) are all amplified at the site. Scour pits 0.8 m depth inshore and 0.4 m depth offshore of the wreck are developed in response to hydrodynamic forcing. Time‐lapse bathymetric surveys quantify seasonal geomorphological change at the Fougueux . Up to 1.2 m of sediment is deposited and 0.7 m of sediment eroded in response to seasonal wave climate variation (an increase of 0.5 m for mean significant wave height, 0.9 m for significant wave height corresponding to 99% of nonexceedance probability, and 0.4 m·s −1 for mean near‐bed orbital velocity during winter conditions). A two‐dimensional scour model reproduces observed seasonal scour changes. Results have direct applications at all stages of a wreck site investigation.